Penilaian Kinerja Karyawan Menggunakan Key Performance Indicator (KPI) pada PT. Hilfic - Happy Lailatul Fitriana; Ilfan Feriantono; Sofriyah izzatul Laily; Ribangun Bamban Jakaria (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
In the#world of work assessment, it is very important, every organization will develop the best strategy to be able to compete. Especially in improving employee performance. The background to good employee performance is the ability to adapt, having skills that are relevant to the job, and the willingness to continue learning and developing. Thus, companies can achieve brand goals more effectively and efficiently. Similar to other companies, PT. Hilfic also carries out performance assessments of its employees. In this research, employee performance assessment uses a strategy based on Key Performance Indicators (KPI). The aim of this research is to identify factors that influence employee performance, such as motivation, competence, work environment, etc. The method used uses qualitative methods. The research results show that there is a positive and significant influence on employee performance, especially on quality and quantity after the company implemented Key Performance Indicators (KPI) as an assessment of its performance.